Understanding the impact of nurses' perception and technological capability on nurses' satisfaction with nursing information system usage: A holistic perspective of alignment. (April 2016) - Lin, Hsien-Cheng; Chiou, Jeng-Yuan; Chen, Chia-Chen; Yang, Chen-Wei
Abstract: Based on the holistic perspective of 'alignment', evaluating the alignment of human–computer interaction is crucial to ensure effective information system implementation and a positive impact on performance. This study aims to examine the impact of alignment between the nurses' perception of NIS (Nursing Information System) performability and technological capability of NIS achieving success on nurses' satisfaction and nursing care performance through the perspectives of alignment as covariation and alignment as profile deviation. A quantitative method and a cross-section design were used to collect data from 531 registered nurses in Taiwan. The results indicate that the coalignment of nurses' perception of NIS performability and the technological capability of NIS achieving success has a positive impact on nurses' satisfaction with NIS usage. Consequently, nurses' satisfaction will increase with the improved performance of nursing care. The results of this research will help the management of NIS application and development within the context of nursing care. Highlights: The alignment of NP-TC is a critical factor; it determines nurses' satisfaction with NIS usage. Nurses' satisfaction with NIS usage has a positive impact on nursing care performance. Supervisors should use a holistic perspective of alignment of NP-TC to improving the nursing care performance.